The Effect of Dyspepsia and Oral Hygiene Practices on the Risk of Tooth Wear in Adolescents - Munandar, Arief; Santi, Tahara Dilla; Zakaria, Radhiah; Abdullah, Asnawi; Hermansyah, Hermansyah (Cakradonya Dental Journal, 2025)
Dyspepsia is a common symptom often observed in adolescents due to digestive disorders, which can affect their eating patterns and lifestyle habits. Additionally, suboptimal oral hygiene practices may increase the risk of tooth wear. Although tooth wear is a normal physiological process, it is considered pathological when it occurs rapidly and excessively. This study aims to analyse the influence of dyspepsia and oral hygiene practices on the risk of tooth wear in adolescents. The methodology employed is a descriptive analytical approach with a cross-sectional design, conducted at SMA NEGERI 1 Kluet Tengah on July 15-16, 2024. Data collection involved 128 students from grades 1-2 through questionnaires and clinical examinations. Out of this number, 117 respondents met the inclusion criteria. Statistical analysis was performed using logistic regression, which revealed a significant influence between dyspepsia and tooth wear (p = 0.000; OR: 1; 95% CI: 0.05-0.20) as well as between oral hygiene practices and tooth wear (p = 0.012; OR: 0.03; 95% CI: 0.001-0.440). Based on the findings, it is recommended that students with a history of dyspepsia undergo dental health check-ups routinely at least every six months.